RNA interference: a chemist's perspective - Gaynor, James W; Campbell, Barry J; Cosstick, Richard (Chemical Society reviews, 2010)
Since the first unequivocal description of RNA interference (RNAi) in 1998, it has remained one of the hottest topics under investigation, culminating in the award of a Nobel Prize to its discoverers in 2006. Excitement over this technique derives from the ease with which it can be used to switch-off a specific gene in almost any organism, thereby allowing the role of that gene to be identified. More importantly, it offers the potential to treat certain diseases by switching-off the causative genes. Key to the RNAi pathway are the small-interfering RNAs (siRNAs), which at 21-23 nucleotides in length are very amenable to analogue development by chemists. However in comparison to the use of oligonucleotides as antisense agents, an area where many chemists first developed an interest in nucleic acids, the RNAi pathway is exceedingly complex. The literature is also complicated by the fact that the phenomenon has been studied in a wide range of organisms. In this tutorial review we have presented the subject from a more chemical perspective, incorporating a glossary to give a clear explanation of the specialist terms. However, the coverage of the biology remains sufficiently detailed to give the reader the necessary insight that we believe will be essential for the successful design of chemically modified siRNA. Covering all the bases of RNA interference: discovery, mechanism, molecular biology, therapeutic potential, siRNA structure and delivery.